PERENCANAAN SISTEM PEMBELAJARAN PAI BERBASIS PBL DAN DIFERENSIASI: ANALISIS KRITIS MODUL MUAMALAH RIBA KELAS VIII SMP DAN REKOMENDASI PENGUATANNYA SESUAI KURIKULUM MERDEKA - Dzikry Ilahana, Anjani; Muhammad Bahrul Ulum; Dinda Annisa Risqi; Moh. Nasrudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study critically analyzes the PAI teaching module for grade VIII SMP/MTs titled “Menjadi Pribadi yang Dapat Dipercaya serta Terhindar dari Riba dalam Jual Beli dan Hutang Piutang” developed by Masrukhi, M.Pd.I in 2025. The research examines the alignment of the module’s components with systematic instructional planning, Project Based Learning (PBL), differentiated learning, and the Merdeka Curriculum (Hamalik, 2009; Pane, 2025). Through qualitative document analysis, the findings reveal strengths in integrating cooperative learning strategies such as Numbered Head Together and Profil Pelajar Pancasila. However, notable weaknesses persist in the formulation of learning objectives that have not fully adhered to SMART criteria, incomplete assessment rubrics, and insufficient differentiation strategies for students with varying abilities (Hastuti & Sahnan, 2025; Safitri et al., 2025). This study proposes concrete recommendations to enhance the module’s effectiveness in fostering students’ understanding and attitudes toward avoiding riba practices in daily economic transactions. The results are expected to contribute to the broader improvement of PAI teaching modules in junior high schools (Prahayuningtiyas & Rindaningsih, 2025).